The time trap - Mackenzie, R. Alec (AMACOM, 1997)
From the hands-down authority on time management techniques, here is a completely updated edition of the national bestseller. "The Time Trap" is filled with smart tactics, hard-hitting interviews, and handy time management tools to help you squeeze the optimal efficiency--and satisfaction-- out of your workday. Plus, you'll discover practical solutions for pinpointing and combatting the Top Twenty Time Wasters!